INTELLIGENT CONTROL SYSTEM FOR THE CATALYTIC REFORMING PROCESS - Abdulazimova Kamila Dilmurod qizi (Journals Park Publishing, 2024)
The catalytic reforming process is a critical industrial operation that produces high-octane gasoline blending components from low-octane petroleum naphthas. It has been a mainstay of petroleum refining for decades due to its high efficiency and product value. However, the process is also highly complex with many interrelated factors that can impact product yields, quality and equipment safety if not carefully controlled. This article proposes the development and implementation of an intelligent control system to help optimize and safeguard the catalytic reforming unit.
Keywords: production, process, substance, hydrogen, modification, control system.